Does poverty influence prevalence of child labor in developing countries? - Abdullahi, Idris Isyaku; Mohd Noor, Zaleha; Said, Rusmawati; Baharumshah, Ahmad Zubaidi (EconJournals, 2016)
The present article examined the impact of poverty on child labour prevalence across 42 developing countries based on system-GMM technique. The main result on the linkage between child labour prevalence and poverty deviated from the popular beliefs in majority of the existing literature that poverty caused child labour prevalence. The finding indicated that poverty is negatively related to child labour prevalence, in the sense that the higher the poverty the lower the child labour prevalence in the sample countries investigated, this finding therefore reconfirmed the wealth paradox of Bhalotra and Heady (2003).